Inferior oblique muscle thickness in Asians - Yasuhiro Takahashi (Dove Medical Press, 2008)
Yasuhiro Takahashi1, Hirohiko Kakizaki2, Takashi Nakano3, Ken Asamoto3, Masayoshi Iwaki21Department of Ophthalmology and Visual Sciences, Osaka City University Graduate School of Medicine, Asahi-machi, Abeno-ku, Osaka, Japan; 2Department of Ophthalmology; 3Anatomy, Aichi Medical University, Nagakute, Aichi, JapanAbstract: The purpose of this study was to examine the inferior oblique muscle (IOM) thickness in Asians by the quasi-sagittal plane of the orbits. Specimens were examined from 23 orbits of 18 Asians (9 orbits in males, 14 in females), aged 63 to 97 years at death. All specimens were fixed in 10% buffered formalin before use. The orbital contents were incised parallel to the optic nerve, after which the lengths of both short and long axes of the IOM were measured and the ratio of short to long axes was calculated. The mean lengths of each short or long axis of the IOM were 2.27 ± 0.49 mm and 7.23 ± 0.97 mm, respectively. The average ratio was 0.32 ± 0.07. There were no significant differences in laterality or gender. This study determined the normal IOM thickness in Asian cadavers, the outcome of which could be useful for detection of IOM involvement in Graves’ orbitopathy.Keywords: inferior oblique muscle, Asian, thickness, quasi-sagittal plane